THE INTEGRATION OF THE AGRICULTURAL SYSTEM CASSAVA INDUSTRIALIZATION IN TRENGGALEK REGENCY, EAST JAVA PROVINCE, INDONESIA - Ida Syamsu Roidah; Djoko Koestiono; Budi Setiawan; Ratya Anindita (Socio-Economics/Agribusiness Department, 2019)
Agribusiness systems are the main driver of agricultural industrialization; thus, there must be coordination and integration between interrelated subsystems. The study aims to analyze the relationship between the agribusiness subsystems to encourage the success of cassava industrialization. Respondents were chosen using the simple random sampling technique and 200 people were involved in the study. The analytical method was the Tobit Regression Model. The results of the study show that the agribusiness subsystem must involve various agribusiness subsystems. Industrialization of agriculture is said to be successful with the linkages between the subsystems, including the input subsystem, production subsystem, processing subsystem, marketing subsystem, and supporting subsystem.